Efektivitas Peran Bappeda dalam Penyusunan Rencana Strategis (RENSTRA) terhadap Pembangunan Daearah Kabupaten Simeulue - Amin, Yahdi (Medan Resource Center, 2023)
This study examines the effectiveness of Bappeda's role in the preparation of the strategic plan for the Simeulue administrative region. Using a qualitative method, data was collected through interviews and document analysis. The study finds that while Bappeda has provided guidelines and regulations for the preparation of the strategic plan, there is still a gap between planning and financing, particularly in the regional development work. This gap is evident in the preparation of the Regional Medium-Term Development Plan (RKPD) and the General Policy and Temporary Budget Ceiling (KUA-PPAS). The study suggests the need for improved coordination and integration between planning and budgeting processes to enhance the effectiveness of Bappeda's role in the strategic planning process. This research contributes to the understanding of the challenges in the preparation of development plans and offers insights for policymakers to enhance the effectiveness of Bappeda in the region.